Inapparent decrease in phytoplankton biomass accompanied by significant size composition succession in the shellfish aquaculture farm in the western Taiwan strait - Mo, Yu; Li, Aifeng; Luo, Zhaohe; Jia, Cun; Ou, Rimei; Qiu, Jinli; Chang, Xinyu; Huang, Hao; Wang, Lei (Frontiers in Marine Science, 2023)
We conducted an annual monthly sampling in the aquaculture areas of Lianjiang and Zhangpu, Fujian province, in the west coast of the Taiwan Strait, to gain insight into the effects of shellfish aquaculture on total phytoplankton biomass and its distribution in phytoplankton size fractions. We observed that the total chlorophyll-a (TChl-a) concentration was higher in Zhangpu (annual mean 2.690 ± 2.375 μg/L) than in Lianjiang (annual mean 1.700 ± 1.500 μg/L) and that Lianjiang had a high N/P ratio during the study, which may have been the main reason for the differences in phytoplankton biomass between the two shellfish aquaculture areas. The response of phytoplankton to shellfish aquaculture was different in the northern versus southern areas. During the aquaculture period of Lianjiang, the TChl-a concentration of surface water was approximately 14% lower than that of bottom water, and such a decreasing trend of Chl-a concentration was consistently present in micro-, nano-, and pico-size fractions. Phytoplankton depletion was not observed during investigation in Zhangpu, which showed highly variable in environmental factors. The contribution of pico-sized Chl-a to TChl-a is evaluated by shellfish aquaculture to some extent in Lianjiang. The shift from the dominance of nano-phytoplankton to the dominance of micro- phytoplankton and pico-phytoplankton was caused mainly by seasonal variation in environmental conditions. In complex marine environments, the distribution of phytoplankton biomass in phytoplankton size fractions showed no significant response to shellfish aquaculture.